Einheit der Kirche im Neuen Testament Dritte europäische orthodox-westliche Exegetenkonferenz in Sankt Petersburg, 24.-31. August 2005 - Niebuhr, Karl-Wilhelm; Alexeev, Anatoly A.; Karakolis, Christos; Luz, Ulrich; Alexeev, Anatoly A.; Karakolis, Christos; Luz, Ulrich (Mohr Siebeck, 2008)
The Unity of the Church in the New Testament. The Third European Orthodox-West Symposium of Exegetes in St. Petersburg from August 24 to August 31, 2005.
PublicationDate: 20080207
Keywords: Hermeneutik -- Mission -- Ekklesiologie -- Eucharistie -- Neues Testament -- Array